Motives of participation in Paraná School Games of students-athlets in Brazil - Grubertt, Guilherme Alves; Cavazzotto, Timothy; Junior, Arnaldo Vaz; Mouad, Mariana; Dib, Luiz Roberto Paez; Junior, Helio Serassuelo; Dourado, Antônio Carlos (Cuadernos de Psicología del Deporte, 2020)
A sports practice for young people has been shown as an important tool in searching for physical, psychological and social benefits. However, some international surveys pointed out that only one part of the children and youths practice sports with some regularity, and that those who start a sports practice, there is a high rate of abandonment. In this sense, experts point out that understanding the reasons that lead to a sport practice can be an important way to understand this phenomenon, especially for the school athlete. Thua, the objective of this study was to identify the reasons for sports practice of school athletes in different sports modalities participating in the School Games of Paraná - 2016 and the variables, gender, age, and training time. In total, 2014 school athletes (1050 girls and 964 boys), aged 10 to 17, participated in the study. The results demonstrate that school athletes gave greatest importance to aspects related to improvement in technical skills, tackling challenges and exposure to risks, learning new skills, and moving to a higher level.